2007
DOI: 10.1007/s00464-007-9267-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transhiatal esophagectomy: outcomes

Abstract: Laparoscopic transhiatal esophagectomy is a safe alternative for experienced professionals. This access can improve mortality, hospital stay, and other outcomes when compared with open methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…5 The need to reduce this morbidity has led to the development of minimally invasive techniques for performing each of the 3 types of esophagectomy. 8,9 Owing to the technically demanding nature of this procedure, access to minimally invasive esophagectomy (MIE) has been limited to select specialized centers that have been able to show comparable results. However, such high-volume centers tend to advocate a specific minimally invasive technique, such as Ivor Lewis or transhiatal esophagectomy, reflecting the learning curve and experience of each institution.…”
mentioning
confidence: 99%
“…5 The need to reduce this morbidity has led to the development of minimally invasive techniques for performing each of the 3 types of esophagectomy. 8,9 Owing to the technically demanding nature of this procedure, access to minimally invasive esophagectomy (MIE) has been limited to select specialized centers that have been able to show comparable results. However, such high-volume centers tend to advocate a specific minimally invasive technique, such as Ivor Lewis or transhiatal esophagectomy, reflecting the learning curve and experience of each institution.…”
mentioning
confidence: 99%
“…In total 8 studies remained available for analysis, of which 4 were comparative cohort studies [14][15][16][17] and 4 were noncomparative cohort studies. [18][19][20][21] The results of the critical appraisal to assess the methodological quality of the comparative studies are shown in Table 1. None of the included studies performed a prospective calculation of the sample size nor were patients randomized.…”
Section: Eligible Studiesmentioning
confidence: 99%